A Refrain for Jane Doe - Choe, Ashley (Ars Medica, 2022)
A Refrain for Jane Doe is a commentary through poetry on some of the conflicting emotions we feel as physicians caring for patients that affect us. It addresses the need to share the story of a patient that has impacted our career or life in the face of the necessary restriction of not being able to say their name – lending to a depersonalization of our patients. It reflects on how we may silently pour ourselves into the people we care for until we lose ourselves because of that depersonalization. It also reflects on the distance we may place between ourselves and our patients as a result – where we may know patients’ problems without remembering their names.